Swedish electoral data 1911-1944 - Berglund, Sten (Umeå University, 1986)
The data collection consists of data from all parliamentary elections during the period 1911-1944. There are also information about changes made in the boundaries of municipalities during this period. A similar study is Electoral Data Archive 1948 - 1970 (SND 0148).

Materialet består av data från samtliga riksdagsval under perioden 1911-1944. Det finns också information om ändringar av administrativa områden under perioden.

Liknade datamaterial finns i Valdataarkivet 1948-1970 (SND 0148).
Svenska valdata 1911-1944
Keywords: elections; val; election data; valdata; Elections; Val; HISTORY; HISTORIA; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap